Unemployment and Nigerian Economic Growth (1985-2009) - Njoku, Asoluka C.; Ihugba, Okezie A. (Richtmann Publishing, 2011)
It is an established economic reality that the size of the workforce directly impacts on a country’s GDP (growth). Notonly does the work force produce manufactured goods or services or agricultural produce in direct proportion, but also brings inits wake increasing purchasing power, which in turn, fuels economic growth. This paper looks at the relationship betweenunemployment and growth in Nigeria (1985-2009). One major findings of the study is that the economy grew by 55.5 percentbetween 1991 and 2006; and the population increased by 36.4 percent. All things been equal, this should have resulted to adecrease in the rate of unemployment but rather, unemployment increased by 74.8 percent. The study also found out that theaverage contribution of the oil sector to the GDP between 1991 and 2006 is 30.5 percent while agriculture that is the mainsource of gainful employment in the country contributed 36.7 percent just a difference of 6.1 percent from that of oil that employsless than 10 percent of the labour force. The study recommends that the agricultural sector as a medium of reducingunemployment in Nigeria should be harnessed and advises that Government and all relevant stakeholders continue in theirquest towards reducing unemployment, as well as give their support in ensuring that the agricultural sector is not downtroddenbut embraced in this task.